Development of Ionic Liquid Based Liquid Phase Microextraction, and Zeolite Imidazolate Frameworks based Sorbent Phase Based Microextraction Combined with Chromatography for Applications in Environmental Analysis - GE DANDAN (2013)
Ph.D